KANDUNGAN MAKNA GURINDAM DUA BELAS KARYA RAJA ALI HAJI - Aderlaepe, Aderlaepe (Universitas Papua, 2018)
Gurindam is a traditional poetry consist of two stanzas and each stanza is built up by two lines/lyrics with the same rhyme. Gurindam Dua Belas is the tittle of the one that consist of twelve parts, written by a famous king of Riau, Raja Ali Haji, at the end of 19th century. Gurindam Dua Belas is the object of this study that aims at describing and analyzing the meaning of the gurindam. Adopted theory to analyze the meaning is semiotic since the gurindam uses various symbols in the stanzas. Through heuristics and hermeneutics reading, the meaning of Gurindam Dua Belas in outline consist of six kinds, namely: religious, advice, offer to behave well, warning, morality message, and unity meanings. Substance of the gurindam is hopefully can be a reference of nation character building nowadays.